The Conceptual Framework of Creative City - Maryunani, Salfitrie Roos; Simatupang, Togar Mangihut; Mirzanti, Isti Raafaldini (Journal of Ecohumanism, 2024)
This study aims to create a conceptual framework, provide variables that make up a creative city, and propose a model that illustrates the idea. This study discovered three primary variables in constructing a creative city: culture, creativity, and creative economy. The article’s novelty derives from the fact that this study looked at both viewpoints of a creative city, firstly, as a place of culture and secondly, as a place of economy and commerce. The article concludes with a set of proposed activities for further operationalization.